Measurement of badminton racket deflection during a stroke - Kwan, M.; Cheng, C. L.; Tang, W. T.; Rasmussen, J. (Sports Engineering, 2010)
The compliance of a badminton racket is an important design consideration, which can be better understood by studying the deflection behaviour of the racket during a stroke. Deflection can be measured using direct methods, such as motion capture or high speed video, or by indirect methods, which then require a mathematical model in order to calculate the deflections from indirect measures. Indirect methods include strain gauges and accelerometers. Here, racket deflection is measured directly using motion capture and compared with deflections calculated from strain gauge data using a beam model. While the elastic behaviour is better calculated from strains than measured by motion capture, it is not possible to extract the whole motion of the racket from strain data. Motion capture is therefore also necessary to determine the rigid body velocity, in order to put the elastic velocity (as calculated from strains) in perspective.